A Survey of metaheuristic approaches for curriculum based course timetabling problem - Wahid, Juliana; Mohd Hussin, Naimah (2017)
Purpose - The aim of this paper is to explore approaches applied for solving CBCTT by presenting features of implementation related to it.The idea is to prepare references structure for future implementation.There are numerous surveys related to approaches in University course timetabling problem (UCTP) (Babaei, Karimpour, & Hadidi, 2014; Nandhini & Kanmani, 2009).Usually surveys that carried out involved post enrollment course timetabling problem (PECTT) and curriculum-based course timetabling problem (CBCTT) together in one literature. Sometimes the depth of information tend to be reduced as both version need to be highlighted at the same place.This can leads to confusing of references in implementation of new approach in terms of features that each versions support. The review of available approaches in solving CBCTT problem in this paper produces information that can be used for future development and experimentation such as number of instances that should be used, neighborhood structure(s) that can be applied and number of experiment repetitions.As stated by Wolpert & Macready (1997) that there is no unique ‘best’ algorithm which performs better than any other algorithm on every test problem (data instance), hence, this paper provides guidelines for future investigation on solving CBCTT problem using other metaheuristic techniques or approaches.